The Impact of Carbon Emission and Renewable Energy on Health Expenditure in Pakistan: https://doi.org/10.55966/assaj.2025.4.1.058 - Dr. Faiza Hassan; Mushtaq Ahmad; Adnan Feroz Khan (`, 2025)
Climate change and air pollution are global challenges with substantial threats to public health. Extended exposure to CO2 can result in a range of negative health effects and illnesses leading to increased health expenditures. This study explores how carbon emissions and the usage of renewable energy affect Pakistan’s per capita health expenditures from 2000 to 2021. The 2SLS-ARDL method is deemed suitable to address potential endogeneity and due to existence of severe multicollinearity. The findings indicate significant positive association between carbon emissions and health spending both in short and long-run. Conversely, renewable energy consumption instrumented by its first lag) shows a negative association with health expenditures per capita both in short & long run. Therefore, promoting environment friendly and sustainable energy-favorable policies, along with limiting CO2 emissions are recommended steps in terms of reducing health costs. Key words: Carbon emissions, Renewable energy consumption, Health expenditures, Pakistan,